1999
DOI: 10.1592/phco.19.9.713.31540
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of 4‐Aminopyridine in Humans with Spinal Cord Injury: A Long‐Term, Controlled Trial

Abstract: Long-term oral administration of immediate-release 4-AP was associated with improvement in and recovery of sensory and motor function, enhanced pulmonary function, and diminished spasticity in patients with long-standing SCI. 4-Aminopyridine appears to be safe and relatively free from toxicity when administered orally over 3 months. Each patient who received immediate-release 4-AP 30 mg/day showed a response in one or more of the outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 26 publications
1
89
1
Order By: Relevance
“…Clinicians equate improvement with quantitative measures while subjects may perceive general positive changes due to an increase in energy level and mood. Segal et al 32 reported enhanced pulmonary function in SCI subjects after 4-AP. Walking efficiency, which was not measured in the present trial, may be worth future study.…”
Section: Discussionmentioning
confidence: 98%
“…Clinicians equate improvement with quantitative measures while subjects may perceive general positive changes due to an increase in energy level and mood. Segal et al 32 reported enhanced pulmonary function in SCI subjects after 4-AP. Walking efficiency, which was not measured in the present trial, may be worth future study.…”
Section: Discussionmentioning
confidence: 98%
“…4-AP and its analogs have numerous clinical applications, including treatment of neuromuscular and neurodegenerative disorders and traumatic injuries of the CNS (Li and Zhang, 1994;Pinter et al, 1997;Fujihara and Miyoshi, 1998;Gruner and Yee, 1999;Segal et al, 1999;Andreani et al, 2000). All of the therapeutic activities of 4-AP are currently explained by blockade of voltageactivated K ϩ channels (Vislobokoe et al, 1983;Davies et al, 1991;Choquet and Korn, 1992;Kirsch and Drewe, 1993;Castle et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports address the beneficial role of 4-AP and related compounds in multiple sclerosis (Schwid et al, 1997;Fujihara and Miyoshi, 1998), myasthenia gravis (Li and Zhang, 1994), and in the canine model of motoneuron disease (Pinter et al, 1997). Clinical applications of 4-AP have been extended to traumatic spinal cord injury (Segal et al, 1999) and to neurodegenerative disorders such as Alzheimer's disease (Andreani et al, 2000). In all these instances, 4-AP has been thought to improve symptomatology through the blockade of voltage-activated K ϩ channels, in turn, causing neuronal depolarization and potentiation of neurotransmission (Smith et al, 2000).…”
mentioning
confidence: 99%
“…Unfortunately, research regarding its efficacy in SCI has been inconclusive. Although animal models and some early studies reported improvement in function and sensation, subsequent randomized, placebo-controlled studies have not demonstrated clinically significant benefits [16][17][18][19][20][21][22]. Summative interpretation of these results is difficult due to small numbers, mixed patient populations and variations in duration, dosage, and mechanism of administration.…”
Section: Introductionmentioning
confidence: 99%